leaf C based defences experiment Dryad - Piper, Frida I; Gundale, Michael; Fuenzalida, Tomás; Fajardo, Alex (Dryad Digital Repository, 2019)
Leaf concentrations of total polyphenols and tannins in juvenile trees of Nothofagus pumilio and N. betuloides subjected to three levels of defoliation during three years.